The phonology of English as an international language: New models, new norms, new goals - Jennifer Jenkins (Oxford Univ. Press, 2000)
This book explores the phonology of English from an interational perspective. It advocates a new approach to English pronunciation teaching in which the goals is mutual intelligibility among non-native speakers, rather than the imitation of native speakers.